Regional investment under uncertain costs of location - Udo Broll; Antonio Roldán-Ponce; Jack E. Wahl (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2012)
Due to globalization competitive firms face increasing economic opportunities for locating their activities in countries, regions and cities that provide the best business environment for their specific needs. In our study we focus on the impact of economic risk and risk preferences upon regional allocation of investments. The source of risk stems from the difference in stochastic costs of location across regions. A comparative static analysis shows that capital allocation depends upon the firms' risk preferences. As a result regional agglomeration of investments may occur although the objective of the regional policy is aimed at the opposite. Our findings demonstrate the suitability of the two-moment approach as an alternative to the expected utility approach. The impact of changes in distribution parameters, such as the expected costs of location, the variance of costs of location and the correlation between locational costs, can be fully characterized via the elasticity of risk aversion. Elements of risk preferences beyond risk aversion prove to be very important to evaluate regional politics. This insight is of interest for empirical research in regional economics.
Keywords: R12; R30; R38; 330; regional allocation; regional economics; regional policy; agglomeration; two-moment decision model; Investition; Standortwahl; Risiko; Kosten; Ballungsraum; Regionalpolitik; Theorie